Ventricular Arrhythmias and K(+) Transfer during Myocardial Ischemia and Intervention with Procaine Amide, Insulin, or Glucose Solution - Regan, Timothy J. (1967)
To assess the relation of ventricular arrhythmias to myocardial K(+) movement during ischemia, we placed an electrode catheter in the left anterior descending coronary artery for thrombus production in intact anesthetized dogs. (85)Kr injections distal to the thrombus permitted serial coronary blood flow measurements. Animals of Group I with a moderate flow reduction exhibited no arrhythmia or myocardial egress of K(+). In Group II, marked flow reduction was accompanied by an injury potential and loss of K(+) from the ischemic site, before and during ventricular tachycardia. Therapeutic interventions were performed in animals having the same degree of ischemia as Group II. Systemic procaine amide in Group III interrupted the tachycardia and egress of K(+), despite persistent ischemia. Group IV did not respond to intracoronary insulin with K(+) uptake, as did normal dogs, and progressed to fibrillation. During the production of hyperglycemia in Group V, myocardial loss of K(+) ceased with maintenance of sinus rhythm. Hemodynamic factors did not appear to have a major role in the genesis of the arrhythmia. Since intracoronary infusion of K(+) in normal dogs similarly altered repolarization and produced fibrillation, it would appear that during ischemia egress of K(+) before development of the arrhythmia indicates a major role of the ion in pathogenesis. This view is supported by the myocardial loss of K(+) and arrhythmia induced in normal dogs by strophanthidin and by the fact that pharmacologic regulation of K(+) loss is associated with correction of the arrhythmia, despite persistence of low blood flow.